THE 1956 REFUGEES AND SOCIAL TRUST IN AUSTRALIA - Bucsi, Anikó (International Journal of Legal and Social Order, 2026)
The first Hungarian arrived in Australia as a convict in the 1820s. The first political refugees were the soldiers of 1848, who arrived in gold-fevered Victoria hoping for a new life. The first humanitarian refugees from Hungary landed in Sydney and Melbourne before the start of World War II. They quickly integrated into Australian society, but they were few in number and did not form separate groups. The two largest waves of Hungarian refugees – cc. 15,000 people each – arrived in the country in the late 1940s and after 1956. There were many of them, and they tried to stay together and establish their own Hungarian communities and institutions in every major city. Some Australians did not look kindly on this, and it took a long time for both sides to accept each other. This presentation, linked to the anniversary of the 1956 revolution, shows the integration process of the 1956 refugees, based on contemporary press articles.